Experimental study on flexural behavior of the BFRC-concrete composite beams. (December 2021) - Zhang, Zhiwen; Abbas, Ebrahim M.A.; Wang, Yi; Yan, Weihua; Cai, Xiaoning; Yao, Shan; Tang, Rong; Cao, Dafu; Lu, Weigang; Ge, Wenjie
Abstract: Three specimens of composite beams were tested under a four-points bending test to study the effect of BFRC height on the flexural behavior of the composite beam. The numerical software MATLAB was used to numerically study the bending moment-curvature ( M-φ ) relationship of the composite beams. The finite element software (ABAQUS) was used to simulate the flexural behavior of the composite beams, and the parameter analysis is carried out to study the effect of strength and height of BFRC, strength and ratio of steel reinforcement on the flexural performance of BFRC-concrete composite beams. The study results show that the flexural capacity of the composite beam is higher than that of the normal concrete beam. With the increase of the height of the BFRC, the flexural capacity increases, and the bottom crack propagation is significantly inhibited. The BFRC height has a negligible effect on the ductility of the composite beam. The results illustrate the assumption of the plane section is valid, and the bonding behavior between steel bar and BFRC as well as the co-working between BFRC and ordinary concrete are perfect. Based on the experimental results, formulae are developed for predicting the cracking, yield, and ultimate moment bearing capacity of the composite beam, and a simplified formula is also developed for predicting the ultimate bearing capacity of composite beam with a balanced reinforcement ratio. The prediction results are consistent well with the test results, and the simulation results exhibit a good agreement with the test results of composite beams.